Median polish for final grades of MTH3000- and MTH4000- level courses - Fitrianto, Anwar; Wijayanto, Hari; Rana, Md. Sohel; Cheong, Yee Voon (Hikari, 2014)
Median polish is a simple and robust method in exploratory data analysis. Median polish is resistant to holes in the table, that is, cells that have no values, but it may require a lot of iterations through the data. This paper describes a technique that uses median polish to observe the relationship between students’ attendance in classes with their performance in the final exam. We found that different attendance percentage in classes can lead to different effect on student’s final exam grades. A student with lower attendance percent age shall get a lower grade in final exam, for overall.